2011
DOI: 10.1007/s11031-011-9251-8
|View full text |Cite
|
Sign up to set email alerts
|

Habitual self-regulatory orientation and ease-of-retrieval: Regulatory focus qualifies the impact of subjective experiences in judgment

Abstract: Eager strategies of self-regulation, known as promotion orientation, and cautious or vigilant strategies of self-regulation, known as prevention orientation, have been found to be associated with distinct patterns of goal attainment and information exploration. Building on these findings, we hypothesize that self-regulation in a promotion versus prevention focus triggers specific patterns of information use in judgment. Specifically, we predict that reliance on ease-of-retrieval-the feeling of ease or difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…prevention or promotion foci) ( Higgins, 1997 ). These systems are aligned with distinct sets of motivations, goals, emotions and behavioural tendencies ( Greifeneder and Keller, 2012;Higgins, 1998 ). While each independent self-regulation tendency may be active at the same time ( Molden et al, 2008 ), individual foci may be habitually or chronically dominant or may be more pronounced than another in response to certain signals or stimuli ( Higgins et al 2001 ).…”
Section: Human Capital Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…prevention or promotion foci) ( Higgins, 1997 ). These systems are aligned with distinct sets of motivations, goals, emotions and behavioural tendencies ( Greifeneder and Keller, 2012;Higgins, 1998 ). While each independent self-regulation tendency may be active at the same time ( Molden et al, 2008 ), individual foci may be habitually or chronically dominant or may be more pronounced than another in response to certain signals or stimuli ( Higgins et al 2001 ).…”
Section: Human Capital Theorymentioning
confidence: 99%
“…Moreover, the operational nature of franchising obligates franchisees to follow established routines and processes to ensure system uniformity, thus restricting autonomy, freedom, and individual creativity (Kaufmann and Eroglu, 1999). When presented with new opportunities, prevention-focused individuals tend to follow the status quo while promotion-focused individuals will tend to be more entrepreneurial and seize recognised opportunities (Greifeneder and Keller, 2012; Liberman and Trope, 1998). Based on the preceding discussion, we argue:…”
Section: Human Capital Theorymentioning
confidence: 99%
“…Previous research has found, for instance, that individuals in a promotion focus are more likely than individuals in a prevention focus to follow their internal impulses, like their affective responses and implicit preferences in deciding which alternative to choose (Florack et al, 2010;Greifeneder & Keller, 2012;Pham & Avnet, 2004, 2009. Indeed, the reliance on affective or implicit responses can be seen as a strategy that matches the eagerness of promotion-focused self-regulation: Reliance on implicit responses and affect is fast and can lead to good decisions (cf.…”
Section: Selective Reliance On Information Sources and Heuristicsmentioning
confidence: 99%
“…promotion-focused) or may be driven by fear and the need to avoid potential loss or fulfil obligations (i.e. prevention-focused) (Das and Kumar, 2011;Greifeneder and Keller, 2012;Lee et al, 2000;Vohs and Baumeister, 2016). While these regulatory patterns may coexist and be active at the same time (Molden et al, 2008), typically, either one of these regulatory foci may be chronically dependent over time, or may be activated in response to external stimuli (Higgins et al, 2001;Mouakhar-Klouz, d'Astous and Darpy, 2016).…”
Section: Economic Uncertaintymentioning
confidence: 99%